Direct costs of occupational asthma due to sensitization in Quebec (1988 to 2002): Revisited - Malo, Jean-Luc (Pulsus Group Inc, 2011)
BACKGROUND: In a previous study, the authors assessed direct costs for occupational asthma (OA) in a random sample of eight to 10 accepted claims per year for OA between 1988 and 2002. Compensation for loss of income (CLI) was found to be significantly higher for men and for OA caused by low-molecular-weight agents. OBJECTIVES AND METHODS: To identify sociodemographic factors that modulate CLI, the dossier of each claimant in the previous study was re-examined. RESULTS: Higher CLI costs were directly related to the duration of CLI (over which loss of income was reimbursed) (r=0.65). Costs of CLI were higher in patients 30 years of age or older at diagnosis, married subjects and individuals who were offered early retirement or were enrolled in an active interventional rehabilitation program. Higher CLI costs in men, but not in women, were associated with the following sociodemographic factors: older age, different rehabilitation program (early retirement and active program versus no specific program) and married status. Older age was found to be significant in the multivariate analysis performed for men. The cost of CLI was higher in workers with OA caused by low-molecular-weight agents. Although proportionally fewer men and younger workers were affected with OA caused by low-molecular-weight agents, the longer duration of CLI for this category of agent could explain the higher costs. CONCLUSION: Higher costs for CLI were associated in men (but not women) with older age, married status and type of rehabilitation program (early retirement and active rehabilitation). Higher costs of CLI for OA caused by low-molecular-weight agents were associated with a longer duration of CLI per se, and not with sociodemographic factors.